Pengaruh Tingkat Intensitas Cahaya Matahari Melalui Naungan Terhadap Pertumbuhan Bibit Gambir (Uncaria gambir Roxb) Varietas Cubadak - Azri Gilang Ramadhan Daulay; Aprizal Zainal; Benni Satria; Rangga Arnelio (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2026)
Gambir (Uncaria gambir Roxb.) is an important Indonesian export commodity used in the pharmaceutical, food, and leather tanning industries. The Cubadak variety is one of the superior varieties with high flavonoid and tannin content and resistance to pests and diseases. One of the obstacles in gambir propagation is uneven seedling growth, which affects plant productivity and quality. One approach to address this issue is by regulating light intensity through shading during the gambir seedling phase. This study aims to investigate the effect of shading intensity on the growth of Cubadak gambir seedlings. The study was conducted at the Experimental Garden of the Faculty of Agriculture, Andalas University, using a Completely Randomized Design (CRD) with four levels of shading intensity (40%, 50%, 60%, and 70%) and three replications. Data were analyzed using an F-test at the 5% level, followed by Duncan’s New Multiple Range Test (DNMRT) at the 5% significance level. The results of the study indicated that 60% shading provided the best effect on gambir seedling growth, as evidenced by increased plant height, number of leaves, leaf area, and other morphological and physiological parameters. A shading intensity of 60% is recommended as the optimal condition for the growth of Cubadak gambir seedlings.